Econometric Modelling of the Innovation Process in Uzbekistan - Farkhod, Mulaydinov (International Journal of Psychosocial Rehabilitation, 2020)
This paper is dedicated to the analysis of factors affecting innovation in Uzbekistan taking the case of the Joint Stock Company “Uzkimyosanoat”. It involved obtaining primary data for 10 enterprises in the company and analysing this data. Factors to be looked at were chosen as research and development, intellectual knowledge, human abilities, level of satisfaction, demand for changes, usage of ICT and product development, growth of enterprise. The results showed that after econometric analysis only 4 out of 8 the chosen factors had a significant effect on the innovation process in the enterprises of “Uzkimyosanoat”. These were intellectual knowledge, R&D, product development and enterprise growth levels. In order to develop innovation in the enterprise effectively, these factors need to be looked at more carefully and policies undertaken to increase their development.